Stepwise Deconvolution of Thermoluminescence Glow Curve - Morales Castillo, Javier; Tercero Gómez, Victor Gustavo; Castaño Maneses, Victor Manuel (Universidad Autónoma de Nuevo León, 2023)
Thermoluminescence (TL) is a property of some materials utilized to measure the radiation dose in a material exposed to a radiation source for a period of time. Dosimeter is based in the measure of the light that a material emit when it is heated after radiation. The TL response in a material can be derived by the band gap theory of solids. In this work, glow curves are modeled following a deconvolution process using Gaussian curves sequentially. One by one, Gaussian curves are added, and every time one is added, manual fitting is carried to provide an initial solution followed by computer optimization. The process repeats until their contribution of new Gaussian curves in reducing the fitting errors is no longer significant and the behavior of errors is considered stable. To illustrate the methodology, glow curves from diamond like carbon are analyzed. The deconvolution method is carried and explained step by step until an acceptable fit is found. In addition, a relatively simple linear prediction approach to perform interpolation is proposed and discussed. Physical implications of the modeled phenomena of electrons traps are discussed for each deconvolution peak and the corresponding energy levels are measured.